Escenarios sociales en las terrazas del alto fucha (2020)
Some Latin American cities such as Bogotá have great shortcomings regarding this issue and this has caused problems related, for example, to the safety or quality of life of the citizen. Bogotá is not the worst-case scenario, but it does present a rather worrying situation in some sectors. The ?Alto Fucha? located in the town of San Cristóbal represents one of these sectors with sufficient flaws in terms of public space and equipment. Although his community has a broad organizational power, the procurement and management of the public has been very difficult. Its informal origin has not been very helpful either because the District has disregarded the sector and it has not been until recently, that it will be legalized in many of the neighborhoods, that public works have been presented to provide them with adequate infrastructure. There are many initiatives that the inhabitants have been carrying out for some time, but they need spaces to develop them. Consequently, due to the lack of a good public space and taking advantage of the great organizational power of the community, a project is proposed that will provide the inhabitants of the upper ?Fucha? where they can gather. The project also addresses the mitigation of landslide risk, faces a hostile topography and, of course, the aim to strengthen the relationship with the river and nature. There is a special intention to promote communication and the establishment of ties and relationships between the ?Alto Fucha? community that will then spread throughout the city. Therefore, the project focuses on assessing the existence of places of public use for the enjoyment of all, this part of the specific needs of the groups of the sector for the means of architectural intervention increases community cohesion.